2018
DOI: 10.1210/jc.2018-00570
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Polycystic Ovary Syndrome Is Associated With Hypertension: A Northern Finland Birth Cohort 1966 Study

Abstract: Context Polycystic ovary syndrome (PCOS) is associated with many traditional cardiovascular disease risk factors, but it is unclear whether PCOS is an independent risk factor for hypertension. Objective To investigate in a population-based setup whether PCOS associates with the risk of hypertension independently of body mass index (BMI) and with cardiovascular manifestations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Women with PCOS did show the accumulation of several metabolic risk factors, namely, high BMI, HOMA-IR, and hs-CRP. Moreover, studies from this cohort report a higher rate of type 2 diabetes (T2D), hypertension, and dyslipidemia in affected women [27,41,42]. Our results revealed that, despite these metabolic derangements, women with PCOS have an adequate vitamin D status compared with the controls.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Women with PCOS did show the accumulation of several metabolic risk factors, namely, high BMI, HOMA-IR, and hs-CRP. Moreover, studies from this cohort report a higher rate of type 2 diabetes (T2D), hypertension, and dyslipidemia in affected women [27,41,42]. Our results revealed that, despite these metabolic derangements, women with PCOS have an adequate vitamin D status compared with the controls.…”
Section: Discussionsupporting
confidence: 52%
“…The limitations of our study include the use of self-reported symptoms and diagnosis of PCOS. However, other studies using the present cohort have validated that self-reported symptoms and PCOS diagnosis are reliable in successfully identifying women with PCOS [24,25,26,27,42]. Because hormonal contraceptives can be used to treat PCOS symptoms and those using such regiments were excluded from the study, the true number of PCOS participants may have been underestimated [66].…”
Section: Discussionmentioning
confidence: 89%
“…Waist circumference was measured at the level midway between the lowest rib margin and the iliac crest. Brachial SBP and DBP were measured three times with 1 min interval after 15 min rest by an automated, oscillometric BP device with an appropriately sized cuff (Omron Digital Automatic Blood Pressure Monitor Model M10-IT; Omron, Kyoto, Japan), and SBP and DBP averages were calculated 18. The level of glucose metabolism was classified according to WHO standards,19 based on a 2-hour oral glucose tolerance test (performed at age 46) and a previously established diagnosis of type 2 diabetes 20…”
Section: Methodsmentioning
confidence: 99%
“…In the adjusted model, we decided a priori to include the following covariates: Educational level (high school or less; high school +1‐4 years; high school +>4 years), 33 ethnicity (western; non‐western) 33 and smoking (yes; no) 34 . Baseline BP (continuous) 6‐8 and number of visits (ie every time a BP was measured and registered) were chosen as additional confounders. Baseline BP was chosen as a confounder to take any baseline imbalance between the groups into account, according to Vickers and Altman 35 …”
Section: Methodsmentioning
confidence: 99%
“…The risk of hypertension (HT) in women with PCOS could be associated with body mass index (BMI) 4,5 . Two recent Scandinavian prospective studies confirmed higher systolic and diastolic blood pressure (BP) in premenopausal women with PCOS 6,7 . In a Danish register‐based study, young women with PCOS had an odds ratio (OR) of 1.7 for development of cardiovascular disease including HT 8 …”
Section: Introductionmentioning
confidence: 99%